2002
DOI: 10.2190/5qg0-hvh8-jed0-ml16
|View full text |Cite
|
Sign up to set email alerts
|

Grief Resulting from Euthanasia and Natural Death of Companion Animals

Abstract: Previous research &as shown that human grief reactions to the l o s of a pet are not only very common, but they can also have a serious impact on the owner's physical and emotional well-king (Katcher & Rosenberg, 1979). The adjustment pmeess can be difficult for owners, especially when the owner is faced with the decision of whether or not to have their pet euthanizeà (Cusack, 1988).The purpose of this study was to investigate the variables of the human grief response associated with pet loss in order to incrr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
2
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 21 publications
5
55
2
5
Order By: Relevance
“…In addition, for each of these symptoms, the rate of endorsement was higher for females than for males. McCutcheon and Fleming (2002) found similar results, with females also showing more distress. Wrobel and Dye (2003) note, however, that these data reflect the percent of occurrences of symptoms, and not the intensity of experience.…”
Section: Pet Attachment and Griefmentioning
confidence: 53%
See 1 more Smart Citation
“…In addition, for each of these symptoms, the rate of endorsement was higher for females than for males. McCutcheon and Fleming (2002) found similar results, with females also showing more distress. Wrobel and Dye (2003) note, however, that these data reflect the percent of occurrences of symptoms, and not the intensity of experience.…”
Section: Pet Attachment and Griefmentioning
confidence: 53%
“…At present, there is only a small body of literature that specifically looks at gender and pet loss, with several findings suggesting that females, rather than males, exhibit more distress following the loss of an animal companion (Brown et al 1996;McCutcheon and Fleming 2002;Planchon and Templer 1996;Gage and Holcomb 1991;Gosse 1994;Reynolds 1999). In a study conducted by Wrobel and Dye (2003) using adult participants, results suggested that the strength of attachment to a pet predicted severity of negative emotional symptoms such as guilt, depression, anger, loneliness, and length of grieving process.…”
Section: Pet Attachment and Griefmentioning
confidence: 99%
“…A survey of 103 pet owners in Canada (McCutcheon and Fleming (2002) found that the time to replacement varied from 4 days to 10 years with a median of 4 months. These values were incorporated in a Pert distribution to model the variability in the time to replacement.…”
Section: Replacementsmentioning
confidence: 99%
“…Female pet owners tend to present intense reactions [6,15,22,27,31], while some studies have shown that younger people grieve more severely [1,27,28]. The presence of a family member or close friend can work as a social support, and facilitate acceptance of the loss [9,15,27].…”
mentioning
confidence: 99%
“…Regarding the animals characteristics, some studies have looked at the type of pet lost, but results have been inconsistent [19,22,25,27]. Although cause of death, including the decision to euthanize, has been considered, the area needs further investigation [8,15,19]. To alleviate the symptoms that occur, mental health intervention, such as individual therapy, has been recommended [7,16,22,27,29].…”
mentioning
confidence: 99%